Designing Value-Creating Supply Chain Networks - Martel, Alain; Klibi, Walid; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Focusing on the design of robust value-creating supply chain networks (SCN) and key strategic issues related to the number; location, capacity and mission of supply chain facilities (plants, distribution centers) - as well as the network structure required to provide flexibility and resilience in an uncertain world - this book presents an innovative methodology for SCN reengineering that can be used to significantly improve the bottom line of supply chain dependent businesses. Providing readers with the tools needed to analyze and model value creation activities, Designing Value-Creating Supply Chain Networks examines the risks faced by modern supply chains, and shows how to develop plausible future scenarios to evaluate potential SCN designs. The design methods proposed are based on a visual representation formalism that facilitates the analysis and modeling of SCN design problems, book chapters incorporate several example problems and exercises which can be solved with Excel tools (Analysis tools and Solver) or with commercial statistical and optimization software.
Designing Supply Chains: Key Issues and Opportunities -- Performance Evaluation and Value Creation -- Demand and Supply Planning -- Activity Centers and Facilities in the Supply Chain -- Transportation in the Supply Chain -- Supply Chain Partners -- Supply Chain Network Optimization -- Capacity Planning and Technology Selection.
Keywords: Industrial Management; Production management; Industrial organization; Industrial Management; Operations Management; Industrial Organization